Differential binding of c-Myc and Max to nucleosomal DNA. - Wechsler, D S (1994)
The ability of a transcription factor to function in vivo must be determined in part by its ability to bind to its recognition site in chromatin. We have used Max and derivatives of c-Myc to characterize the effect of changes of dimerization partner on binding to nucleosomal DNA templates. We find that homo- and heterodimeric complexes of these proteins bind to the CACGTG sequence in free DNA with similar affinities. Although Max homodimers bind to nucleosomes, truncated c-Myc homodimers do not. Surprisingly, modifying the c-Myc dimerization interface or changing its dimerization partner to Max enables nucleosomal DNA binding. Thus, changes in dimer structure or dimerization efficiency can have significant effects on nucleosome binding that are not predicted from their affinity for free DNA. We conclude that domains other than the basic region per se influence the ability of a transcription factor to bind to nucleosomal DNA and that changes of dimerization partner can directly affect the ability of a factor to occupy nucleosomal binding sites.